(3CSGSjGJ GdYQV h GdJbOje GdaYGd (B:s (3eONd JWHjbj (B/s - (3GdYdGb, HTjQs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3eONd Gdi YedjI GdYQV h GdJbOje , OhQ GdJUGd aj JaYjd gPg GdYedjI (B: (3GdYdGbI GdbGFeI Hjf caGAI GdGJUGd h fJGFL YedjI GdYQV h GdJbOje , GdGJUGd hab fhY GdQSGdI GdGJUGdjI h hab GJLGgGJg h GdGJUGdGJ ZjQ GdQSejI , THcGJ GJUGd GdaQjb h GdGJUGdGJ GdNGQLjI , CSGdjH GdJYGed eY GdGfeGW GdeNJdaI ddRHGFf (B( (3GdYedGA(B) (3h eJWdHGJ h eQGMd GdYQV h GdJbOje GdaYGd eY hLhO CSFdI ddefGbTI aj fgGjI cd aUd(B.s
(3eQGLY U(B.231s
Keywords: (3GdJShjbs; (3GdYQV h GdWdHs; (3GdeHjYGJs